Apakah Perempuan Indonesia Terbelakang dalam Adopsi Internet? : Temuan Empiris - Fathul Wahid (Teknoin, 2005)
This research aims to (a) investigate differences in Internet adoption; (b) identify factors affecting Internet adoption; and (c) examine differences of Internet usage pattern between male and female users. Using data from 714 respondents/students with various backgrounds, the research unveils that in general, Internet adoption among female users are lower than that among male users.  Using Technology Acceptance Model (TAM), the research also finds that the Internet adoption among female users is affected by perceived ease of use rather than perceived usefulness. On the other hand, the Internet adoption among male users is affected by perceived usefulness rather than perceived ease of use. Male users are found to have a more flexible Internet access venue when compared to female users. The research also gives an evident that Internet usage pattern among male and female users differs. Proportion of female users who use the Internet for chatting and study-related activities is significantly larger than that of male users. Conversely, proportion of male users who use the Internet for reading online news, testing and downloading software, shopping, entertainment, seeking job vacancy, and visiting pornographic sites are larger than female users. High cost Internet access and low access speed of the Internet and a lack of English proficiency are identified to be most severe obstacles of the Internet adoption in Indonesia. Keywords: adoption of Internet, women studies, Indonesia.